Synergistic effect of Canarium strictum leaves extract and KI on the corrosion protection of mild steel in 15% HCl solution - Reema H. Aldahiri; Mahmoud A. Hussein; Soha M. A. Al-Bukhari; Khalid A. Alamry; Ajahar Khan; Ruby Aslam (Scientific Reports)
Abstract The inhibitory potential of an alcoholic extract derived from Canarium strictum leaves (CSL) was evaluated as a corrosion inhibitor for mild steel (MS) in 15% HCl solution. Furthermore, to enhance its inhibition effectiveness, the influence of potassium iodide (KI) was also examined. The corrosion inhibition and adsorption characteristics of CSL were comprehensively analysed through weight loss measurement, electrochemical impedance measurement (EIS), potentiodynamic polarization (PP), UV–visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), atomic force microscopy (AFM), scanning electron microscopy and energy dispersive spectroscopy (SEM–EDS). The effect of temperature and immersion time on corrosion inhibition was also investigated. The studied CSL extract exhibited maximum inhibition efficiency of 92.2% at 700 ppm alone, while adding 5 ppm KI 96.8% inhibition efficiency was observed. Moreover, with KI, an efficiency of 98% was observed at extended immersion of 48 h. The PP results showed that CSL and CSL + KI were good mixed-type inhibitor system. Adsorption data was best fitted to the Langmuir isotherm model, and thermodynamic, kinetic, and surface analyses shed light on the inhibitory mechanism.